Noninvasive Compartmental Pressure Assessment With iCare in Healthy Individuals of Different Ages - Jialiang Guo; Jianfeng Zhang; Kezheng Du; Bo Shi; Weichong Dong; Yingze Zhang; Zhiyong Hou (Orthopaedic Surgery)
ABSTRACT Objective Acute compartment syndrome is a major orthopedic emergency due to elevated pressure in the closed muscle compartment, and prompt evaluation and fasciotomy are always needed. However, the gold standard indicator of fasciotomy is still under debate. To date, few studies have investigated the variations in compartmental pressure at different locations in people of different ages. The aim of the research was to compare compartmental pressure among different age groups and measurement locations. Methods A total of 154 healthy individuals including 106 males and 48 females over 18 years (46.8 ± 14.0 years) were enrolled between January 2020 and December 2021, and classified into five age groups: Group I = 18–30 years; Group II = 31–40 years; Group III = 41–50 years; Group IV = 51–60 years; and Group V ≥ 61 years. Six measurement locations (lower, middle, and upper points, 6 points) were selected to assess pressure variations in the anterior compartment and posterior superficial compartment with the iCare device, which calculates biomechanical properties based on the tissue's inherent response. Differences in pressure among the five age groups and six measurement locations (three for anterior compartment, three for posterior superficial compartment) were examined. One‐way ANOVA and LST tests were used to conduct comparisons among five independent age groups. Results In the same measurement location, the compartmental pressure in Group V at the upper anterior (anterior fascial compartment) measurement location was increased compared with that in Groups I, III, and IV. However, the compartmental pressures at the middle anterior and posterior measurement locations were almost comparable among the five different age groups. In the same age group, the compartmental pressure was more inclined to be lower at the upper anterior measurement location in Groups I–IV. However, no significant differences were observed for other measurement locations. Conclusions The measurement results demonstrated comparable compartmental pressure in the fascial compartment at most measurement locations. The fascia, which forms the limb compartment, may play a role in pressure release or redistribution after injury or fracture due to its function and unique or interconnected structure.